(untitled) (Jurnal Teknologi (Sciences & Engineering), 2022)
The knowledge of the development of temperature profiles in polymer processing machinery is very useful to give a clear picture of the interrelationship between the temperature, rheological characteristics, and the behaviour of the polymer. Using the modified cooled stainless tube (CST) technique together with a modified thermocouple mesh, the temperature profiles of low-density polyethylene (LDPE) in the extruder outlet using an open channel adapter with various screw speeds were investigated. The thermocouple mesh, which was considered easy to build was shown to have outstanding performance in terms of accuracy when obtaining readings for the experiment. From the study, the results indicated that the screw speed and temperature fluctuations are directly proportional.